Transmodern Perspectives on Contemporary Literatures in English, editado por Jessica Aliaga-Lavrijsen y José María Yebra-Pertusa - Flores-Quesada, María Magdalena (Universidad de Zaragoza, 2021)
Esta reseña examina el volumen Transmodern Perspectives on Contemporary Literatures in English, editado por Jessica Aliaga-Lavrijsen y José María Yebra-Pertusa, que propone el concepto de transmodernidad como un nuevo paradigma cultural y crítico más allá del posmodernismo.

This review analyzes Transmodern Perspectives on Contemporary Literatures in English, edited by Jessica Aliaga-Lavrijsen and José María Yebra-Pertusa, which introduces “Transmodernity” as a new cultural and critical paradigm beyond Postmodernism.
La reseña se encuentra en open access
https://papiro.unizar.es/ojs/index.php/misc/about
Keywords: Modernismo (Literatura); Transmodernity; English literature; Critical review; Contemporary literature